Texts : contemporary cultural texts and critical approaches - Childs, Peter, 1962- (Edinburgh University Press, 2006)
Being able to analyse different types of text is an essential skill for students of literature. Texts is a new kind of book which shows students how to use literary theory to approach a wide range of literary, cultural and media texts of the kind studied on today's courses. These texts range from short stories, autobiographies, political speeches, websites and lyrics to films such as The Matrix and Harry Potter and from television's Big Brother to shopping malls, celebrities, and rock videos. Each chapter combines an introduction to the text and aspects of its critical reception with an analysis using one of sixteen key approaches, from established angles like feminism, postcolonial studies and deconstruction to newer areas such as ecocriticism, trauma theory, and ethical criticism. Each chapter also indicates alternative ways of reading the text by drawing on other critical approaches. Texts: is the first student guide to examine visual, virtual and performance texts alongside written texts reflecting the broadening range of the contemporary literature syllabus demonstrates clearly how students can analyse a familiar text in different ways, a core skill which many find difficult provides a student introduction to contemporary culture via well known popular texts and literary theories.